Multi-step subcritical water extracts of fucus vesiculosus l. And codium tomentosum stackhouse: Composition, health-benefits and safety - Soares, Cristina (2021)
Mental health and active aging are two of the main concerns in the 21st century. To search for new neuroprotective compounds, extracts of Codium tomentosum Stackhouse and Fucus vesiculosus L. were obtained through multi-step (four step) subcritical water extraction using a temperature gradient. The safety assessment of the extracts was performed by screening pharmaceutical compounds and pesticides by UHPLC-MS/MS, and iodine and arsenic levels by ICP-MS. Although the extracts were free of pharmaceutical compounds and pesticides, the presence of arsenic and high iodine contents were found in the first two extraction steps. Thus, the health-benefits were only evaluated for the fractions obtained in steps 3 and 4 from the extraction process. These fractions were tested against five brain enzymes implicated in Alzheimer’s, Parkinson’s, and major depression etiology as well as against reactive oxygen and nitrogen species, having been observed a strong enzyme inhibition and radical scavenging activities for the step 4 fractions from both seaweed species. Regarding the variation of the chemical composition during the extraction, step 1 fractions were the richest in phenolic compounds. With the increase in temperature, Maillard reaction, caramelization and thermo-oxidation occurred, and the resulting products positively affected the antioxidant capacity and the neuroprotective effects.